The persistence of gender inequality - Evans, Mary 1946- (Cambridge, United Kingdom Polity Press, 2017)
"Despite centuries of campaigning, women still earn less and have less power than men. Equality remains a goal not yet reached. In this incisive account of why this is the case, Mary Evans argues that optimistic narratives of progress and emancipation have served to obscure long-term structural inequalities between women and men, structural inequalities which are not only about gender but also about general social inequality. In widening the lenses on the persistence of gender inequality, Evans shows how in contemporary debates about social inequality gender is often ignored, implicitly side-lining critical aspects of relations between women and men. This engaging short book attempts to join up some of the dots in the ways that we think about both social and gender inequality, and offers a new perspective on a problem that still demands society's full attention" -- Provided by publisher.
1. What is gender inequality? -- Making inequality -- What has changed? -- Changing conditions -- 2. Worlds of inequality -- Exploiting the feminine -- Problems at work -- Problems of agency -- Locations of inequality -- 3. Problems of subjectivity -- Imagining the female body -- Other bodies -- How the body matters -- Questions of order -- 4. Enter feminism -- Conditions for feminism -- A secondary sex -- Changing times -- Unchanging times -- 5. Making gender equality -- The rights of women -- The limits of liberalism.
Includes bibliographical references (pages 152-165) and index.
Keywords: Sex discrimination; Women's rights; Equality; Sex role